THE RELATIONSHIP OF SELF-CONFIDENCE WITH THE MATHEMATICAL PROBLEM-SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Verminus Verminus; Mohamad Rifat; Asep Nursangaji (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The purpose of this study is to describe the relationship between self-confidence and mathematical problem-solving ability in finding solutions to linear equations among junior high school students. This study utilizes a qualitative approach with a correlational design. The subjects of this study are the 32 students of class VIII D at SMP Negeri 12 Pontianak. The instruments are used including a self-confidence questionnaire and a test on the ability to solve problems related to linear equations. Data analysis employs the Pearson Product Moment correlation. The data shows that the students of class VIII D have a good level of self-confidence in learning mathematics. The majority of these students also possess good mathematical problem-solving abilities. Based on the calculation of the Pearson Product Moment correlation, the obtained correlation coefficient (r-value) between self-confidence and mathematical problem-solving ability for the students of class VIII D at SMP Negeri 12 Pontianak is 0.366, indicating a low correlation. However, there is a positive and statistically significant relationship between self-confidence and mathematical problem-solving ability, implying that an increase in self-confidence tends to correspond with an improvement in students' problem-solving skills.